A regional classification of time spectral amplitudes in total electron content: Southeastern United States during solar cycle 24 - Burkholder, B. L.; Cuellar, R.; Nykyri, K.; Ma, X.; Debchoudhury, S. (Frontiers in Astronomy and Space Sciences, 2022)
To investigate the meso-scale structure (100s of km) of the ionosphere at mid-latitudes, the spectral properties in calculated total electron content (TEC) at a cluster of GPS receivers in and around Florida are analyzed. The ionosphere does not respond exactly the same to periodic solar driving at different locations around the planet, due to the complex electrodynamic interactions of the coupled magnetosphere-ionosphere system. Therefore, at each GPS receiver in the cluster we compare spatio-temporal variations of the spectral amplitudes for diurnal, solar rotation, and seasonal oscillations. The amplitudes for these dominant oscillations are organized with respect to magnetic latitude of the receiver. A low-latitude and high-latitude station are also included to put the mid-latitude ionospheric response into a global context. The amplitudes of diurnal, seasonal, and solar rotation signals are well ordered by magnetic latitude, superposed with meso-scale deviations between stations separated by ∼ 100s of km. The results suggest that spatio-temporal variations of spectral amplitudes in the mid-latitude ionosphere are not dominated by a single process. This conclusion is based on our finding that at high latitude, the shape of the diurnal signal varies significantly less with solar activity compared to low- and mid-latitudes, and additionally, that the ratio of annual to semi-annual amplitudes fluctuates around 1 with time and from station-to-station only at mid-latitudes.